IMPLEMENTATION OF BUSINESS MODEL CANVAS AS A BUSINESS DEVELOPMENT STRATEGY IN MICRO, SMALL AND MEDIUM ENTERPRISES NYEMILINYUKS.ID IN MAKASSAR CITY - FARAH FITRIA RAMADHANI; AGUS SYAM, ASMAYANTI, MUHAMMAD JUFRI, SUMIATI TAHIR (CV. Adiba Aisha Amira, 2026)
A high number of MSMEs should absorb a lot of labor. However, the reality is that some MSMEs are still unable to absorb labor. This happens because many MSMEs do not experience development in their business operations. The development of a business is determined by the ability to plan and implement strategies, as strategies require business owners to think long- term and improve all implementations in a more orderly manner. This research aims to implement the right strategy for the business Nyemilinyuks.id, with the hope of developing the operational aspects of the business being run. The strategic method that will be applied is the Business Model Canvas, which consists of 9 elements: Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. This research is a descriptive (exploratory) qualitative study. Where the object of the study is the Business Model Canvas. This research uses the unit of analysis, which consists of several individuals from the Nyemilinyuks.id business. The type of data examined is qualitative data, which is primary data obtained thru direct observation and direct question-and-answer interviews with the relevant parties, namely the business owner, employes, and consumers of Nyemilinyuks.id. This research employs the purposive sampling method, which deliberately determines or selects the respondents to be studied. The total number of samples is 7 people. The result of this research is to improve and add several elements of the Business Model Canvas (BMC) applied by Nyemilnyuks after analysis, where there are several elements that need to be improved to enhance business operations, help increase product sales, and achieve sales targets, including customer segments, value propositions, customer relationships, channels, key activities, and key partners